Green Compensation Package of HRM Framework and Its Impact on the Supply Chain Management in Bangladeshi Manufacturing Companies’ - Tarnima Warda Andalib; Mohd. Ridzuan Darun; Hasliza Abdul Halim (International Journal of Supply Chain Management, 2020)
This paper aims to analyze Green Compensation Package (GCP) in the HRM framework of Bangladeshi manufacturing companies applying multiple case studies to view if it is mapped with ERS(employee rights) like Universal Declaration of Human Rights(UDHR), International Labour Organization(ILO) and Bangladesh Labour Act (BDL) or not. Here, GCP is observed as an ongoing demand and need of the Employees in any organization. Since, GCP is a primary component of HRM framework, it needs to observed, analyzed and modified when needed based on demand and supply of the skilled employees at necessary units. Green and more humanitarian GCP is suggested in this paper.